An unusual co-crystal [(μ2-dcpm)Ag2(μ2-O2CH)(η2-NO3)]2·[(μ2-dcpm)2Ag4(μ2-NO3)4] and its connection to the selective decarboxylation of formic acid in the gas phase. Issue 48 (24th November 2016) - Zavras, Athanasios; White, Jonathan M.; O'Hair, Richard A. J.
Abstract : Binuclear silver cluster with μ2 -formate and μ2 -dcpm catalyses the decomposition of HCO2 H. This structural motif is present in the crystal. Abstract : ESI/MS of an acetonitrile solution containing a mixture of AgNO3  :  bis(dicyclohexylphosphino)methane (dcpm, L) : NaO2 CH in a molar ratio of 2 : 1 : 1 gave an abundant peak due to [LAg2 (O2 CH)] + and a minor peak assigned as [L2 Ag4 (O2 CH)3 ] + . When this acetonitrile solution was frozen and layered with diethyl ether and left undisturbed for six days, crystalline material suitable for X-ray crystallography was identified and separated from amorphous solids. Single crystal X-ray diffraction revealed an unusual co-crystal consisting of two discrete tetranuclear silver clusters [(μ2 -dcpm)Ag2 (μ2 -O2 CH)(η 2 -NO3 )]2 ·[(μ2 -dcpm)2 Ag4 (μ2 -NO3 )4 ]. While all of the coordinated formates in [LAg2 (O2 CH)] + and [L2 Ag4 (O2 CH)3 ] + can be decarboxylated in the gas-phase under conditions of collision induced dissociation, only the hydride [LAg2 (H)] + thus formed reacts with formic acid via protonation and liberation of H2 to regenerate to formate, thereby closing a catalytic cycle for the selective decomposition of formic acid.